EFEKTIFITAS HASIL BELAJAR PENGGUNAAN MODUL BERBASIS E-LEARNING PADA MATA KULIAH GASTRONOMI - Yulia Mandasari (Jurnal Pariwisata Bunda, 2022)
This research was carried out due to some limitations in gastronomic learning. Teaching and learning contents have not been updated,  and e-learning has not been implemented. As a result, learning outcomes have not achieved as expected. The purpose of this research was to find out the effectiveness of learning outcomes using a learning module on the basis of e-learning on the subject of gastronomy of program study culinary diploma 3 of State University of Padang.  The method used in this research was the Research and Development (R&D) development model Instructional Development Institute (IDI). The subjects of this study  were the students of the Study Program culinary, diploma 3 of  the faculty of Tourism and Hospitality of Padang State University.  The result indicated that the Learning Module on the basis of E-learning was effective. The effectiveness was proved with the average score of experimental group learning outcomes was 81,33 meaning pass, and the control group was 60,16 meaning fail. It can be concluded that there were  significant differences in learning outcomes between the experimental class and the control class. The E-learning module in Gastronomy subject can be utilized to upgrade the student's creativity.